Teaching GIS and strengthening user receptiveness (lifelong learning) - Márkus, Béla; Szepes, András (Acta Agraria Kaposváriensis, 2003)
In our lecture we will talk about the professional postgraduate activity on GIS. We highlight the turning points in our Faculty’s life. We especially emphasize the role and importance of postgraduate courses. We introduce our wide offer of postgraduate courses from the secondary until the advanced level. For every course the guideline can be found at the indicated web pages. At last we mention the public acceptance which also means the recognition of our graduated students.
Keywords: education of geoinformatics; user receptivness